Innovative and entrepreneurial activity stimulation among teachers through personalized monitoring technology - Alekhina E.I., Roshchupkina V.V., Shatskaya E.Y.,; A.V., Lukyanova; P.P, Pivnenko (Opción, 2020)
The article discusses the author’s approaches to innovative and entrepreneurial activity for teacher higher education stimulation on the basis of personalized monitoring technology via the analysis of scientific and pedagogical literature on the topic of research and pedagogical modeling. As a result, the implementation of the developed technology of personalized monitoring in the higher education system contributes to the development of the individual characteristics of a teacher. In conclusion, the psychological state of the teachers who are in the system of personalized monitoring can have a significant impact on the productivity and effectiveness of its innovative and entrepreneurial activities.